Breeding report of a new ornamental peach cultivar Yanfen No. 1 - QIAO Yuxuan; JIAO Xuehui; YUE Changping; SHI Xibing (Guoshu xuebao, 2025)
Yanfen No. 1 is a new ornamental peach cultivar selected from the progeny of a cross between Yanhongzaohua as the maternal parent and Zaotiantao as the paternal parent. In 2013, the hybrid fruits were harvested and the seeds were sown that year, successfully breeding 30 seedlings. In 2015, after the seedlings flowered, excellent individual plants were selected. The initial flowering period of this individual plant is around March 3rd, 14 days earlier than the maternal parent Yanhongzaohua. The peak flowering period is spectacular, with high ornamental value. Subsequently, using peach as the rootstock, grafting propagation were carried out year after year. Characteristics such as flowers, leaves and fruits were recorded, and indicators such as flower diameter, internode length and fruit size were measured. It was found that the progeny traits were stable and consistent with the maternal plant's performance, and it was tentatively named Yanfen No. 1. In 2024, the National Forestry and Grassland Administration reviewed and granted the new plant cultivar right. This cultivar has a medium tree vigor and an open tree shape. The branches are long and straight, and the flower branches are green with red spots. The number of flower buds is medium, with an average of 50 flowers per branch. The internode length is medium, with an average length of 1.53 cm. The buds are deep pink and oval. The flower type is Chinese rose shaped and deep pink, with multiple petals and an average flower diameter of 37.79 cm. The average number of petals is 29, with the middle petals being 17.64 mm long and 9.36 mm wide, in the shape of an elongated oval. The average number of stamens is 47, shorter than the petals. There are 2 to 4 pistils, which are almost the same length as the stamens. The anther is orange-red. There are 10 sepals in two rounds. In Xuchang, Henan province, the initial flowering period is March 3rd, the peak flowering period is from March 8th to 20th, and the post flowering period is at the end of March, with a flowering duration of about 22 days. The fruit is greenish-white, round, and hairy on the skin. It is resistant to drought and cold, with strong resistance. It requires a low amount of chilling, and can be planted in areas where the chilling requirement is 300 to 500 hours.